Interactions with virtual therapists during motor rehabilitation in immersive virtual environments: a systematic review - Crowe, Stephanie Elena; Yousefi, Mamehgol; Shahri, Bahareh; Piumsomboon, Thammathip; Hoermann, Simon (Frontiers in Virtual Reality, 2024)
Virtual Reality applications for rehabilitation are increasing in popularity. In traditional as well as virtual rehabilitation, the guidance of an occupational therapist through physical and verbal interaction is often required. Several studies have attempted to implement a virtual therapist or assistant in immersive virtual environments for rehabilitation.Objective: This research aims to systematically review these studies, understanding the therapist's role and how they are represented in the virtual environment, how the virtual therapist and patient interact and the experience of users. Our goal is to provide guidance for virtual therapist implementations into fully immersive VR environments. Method: The researchers systematically reviewed the literature on virtual therapists in immersive virtual environments for motor rehabilitation (protocol prospectively registered with PROSPERO ID: CRD42022357369).Seven studies were identified, with findings showing that virtual therapists are often human-like avatars that guide patients, requiring them to mimic the therapist's movements. Visual, haptic, or one-direction audio feedback from the therapist to the patient was provided in five studies. The selected studies were all newly developed custom-made systems, with five systems developed using the same game engine. Studies carrying out user testing utilised several methods to understand user experience, evidencing a positive attitude from therapists and motivated and satisfied patients. Future Research: The roles of virtual therapists for motor rehabilitation needs to be explored further in rigorous empirical studies to gather data on patient and therapist user experience. Considerable potential was identified in the development of virtual therapists and therapeutic alliance in the virtual environment. Future systems should reduce manual input from therapists and include personalisation and individualised patient feedback.The formatting preference is British English.